2011
DOI: 10.1007/s00203-011-0711-z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characterisation of recombinant Corynebacterium glutamicum NAD+-dependent LDH over-expressed in E. coli and its rescue of an lldD − phenotype in C. glutamicum: the issue of reversibility re-examined

Abstract: The ldh gene of Corynebacterium glutamicum ATCC 13032 (gene symbol cg3219, encoding a 314 residue NAD+-dependent L-(+)-lactate dehydrogenase, EC 1.1.1.27) was cloned into the expression vector pKK388-1 and over-expressed in an ldhA-null E. coli TG1 strain upon isopropyl-β-D-thiogalactopyranoside (IPTG) induction. The recombinant protein (referred to here as CgLDH) was purified by a combination of dye-ligand and ion-exchange chromatography. Though active in its absence, CgLDH activity is enhanced 17- to 20-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Disruption of l -iLDH resulted in the loss of ability to utilize l -lactate as the sole carbon source [9], [28]. Constitutively expressed NAD-dependent l -lactate dehydrogenase would enable the l -iLDH inactivation mutant of C. glutamicum to grow on l -lactate [29]. In the present study, l -iLDH from P. stutzeri SDM was purified and characterized.…”
Section: Resultsmentioning
confidence: 91%
“…Disruption of l -iLDH resulted in the loss of ability to utilize l -lactate as the sole carbon source [9], [28]. Constitutively expressed NAD-dependent l -lactate dehydrogenase would enable the l -iLDH inactivation mutant of C. glutamicum to grow on l -lactate [29]. In the present study, l -iLDH from P. stutzeri SDM was purified and characterized.…”
Section: Resultsmentioning
confidence: 91%
“…). The nLDH/Etf in A. woodii and l ‐nLDHs in C. glutamicum and Lactococcus lactis were recently reported to enable these microorganisms to grow on l ‐lactate (Sharkey et al ., ; Zhao et al ., ; Schink, ; Weghoff et al ., ). In this study, we first demonstrated that a d ‐nLDH encoding gene ldhA in P. putida KT2440 had no role in its d ‐lactate utilization by mutation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…nLDHs are cytoplasmic proteins that catalyze the conversion of pyruvate to lactic acid in a reversible or irreversible manner. iLDHs are membrane bound, and they catalyze the oxidation of lactic acid to pyruvate (8). Members of these two classes exist in a stereospecific (L-or D-specific) form.…”
mentioning
confidence: 99%